Study of The Parasites of The Local Chickens (Gallus Gallus Domisticus) in Duhok Province, Kurdistan Region-Iraq - Al-Saeed, Adel T. M.; AL-Badrani, Mohammed A. I (Science Journal of University of Zakho, 2014)
One hundred and twenty chickens the local breed (Gallus gallus domesticus) were examined during the period from June to October 2012 in Duhok Province / Kurdistan Region of Iraq. To investigate the prevalence of ecto and endoparasites among them. The recorded parasites included: Two species of lice namely Mencanths stramineus with infestation rates of 34% and Goniocotes gallinae, with infestation rate of 0.8%. One species of soft tick, genus Aragas persicus, was also recorded, with an infestation rate of 4.1%. Whereas, the endoparasite examination revealed 16.6% from protozoa (Eimeria) and the presence of four nematodes and six cestode species, but no trematodes and blood parasites. The highest nematode infection rate was 46.6% with Subulura species, followed by Ascaridia galli with infection rate of 38.3%, Heterakis gallinarum with infection rate of 25% and, Capillaria with infection rate of 4.1%. Regarding cestodes, the recorded species included: Raillietina tetragona, R. echinobothrida, R. cesticillus, Fimbriaria fasciolari, Davainea proglottina, and Amoebotaenia sphenoides with infection rates of 27.5%, 24.1%, 6.6%, 1.6%, 2.5%, and 0.8%, respectively.